Mujer Mas Segura (Safer Women): a combination prevention intervention to reduce sexual and injection risks among female sex workers who inject drugs - Vera Alicia; Abramovitz Daniela; Lozada Remedios; Martinez Gustavo; Rangel M; Staines Hugo; Patterson Thomas L; Strathdee Steffanie A (BMC, 2012)
Abstract Background Female sex workers who inject drugs (FSW-IDUs) are at risk of acquiring HIV, sexually transmitted infections (STI) and blood-borne infections through unprotected sex and sharing injection equipment. We conducted a 2×2 factorial randomized controlled trial to evaluate combination interventions to simultaneously reduce sexual and injection risks among FSW-IDUs in Tijuana and Ciudad Juarez, Mexico. Methods/design FSW-IDUs ≥18 years reporting sharing injection equipment and unprotected sex with clients within the last month were randomized to one of four conditions based on an a priori randomization schedule, blinding interviewer/counselors to assignment. Due to the extreme vulnerability of this population, we did not include a control group that would deny some women access to preventive information. All women received similar information regardless of group allocation; the difference was in the way the information was delivered and the extent to which women had an interactive role. Each condition was a single 60-minute session, including either an interactive or didactic version of an injection risk intervention and sexual risk intervention. Women underwent interviewer-administered surveys and testing for HIV, syphilis, gonorrhea, Chlamydia, and Trichomonas at baseline and quarterly for 12 months. Combined HIV/STI incidence will be the primary outcome. Secondary outcomes are proportionate reductions in sharing of injection equipment and unprotected sex with clients. Discussion Of 1,132 women, 548 (48.4%) were excluded (88.9% were ineligible; 11.1% refused to participate or did not return); 584 eligible women enrolled (284 in Tijuana; 300 in Ciudad Juarez). All 584 participants completed the baseline interview, provided biological samples and were randomized to one of the four groups. During follow-up, 17 participants (2.9%) were lost to follow-up, of whom 10 (58.8%) had died, leaving 567 participants for analysis. This study appears to be the first intervention to attempt to simultaneously reduce injection and sexual risk behaviors among FSW-IDUs. The factorial design will permit analysis to determine whether the combination of the two interactive interventions and/or its respective components are effective in reducing injection and/or sexual risks, which will have direct, tangible policy implications for Mexico and potentially other resource-poor countries. Trial registration NCT00840658